PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN SEBAGAI VARIABEL INTERVENING (Studi Kasus Pada Cus-Cus Cafe Malang) - Ria Wahyu Agustina; N Rachma; M. Hufron (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACT This study aims to find out and analyze the influence of service quality and price on customer loyalty through satisfaction as an intervening variable of Cus-Cus Cafe Malang. The population and samples are Cus-Cus Cafe Malang customers, 92 people. Data collection through questionnaires. Data analysis in this study uses SPSS version 16. The sampling technique uses the explanatory research method and the data testing techniques used in this study include validity test, reliability test, normality test, path analysis, t test, and sobel test. The results of the analysis show that service quality and prices in partial tangible, service quality have a significant effect on satisfaction and prices have no significant effect on satisfaction, service quality and prices have a direct effect on loyalty, service quality variables indirectly influence customer loyalty and satisfaction as intervening variables and prices indirectly have a non-significant effect on customer loyalty with satisfaction as an intervening variable.Keywords: Service Quality, Price, Customer Loyalty and Satisfaction.